Multi-material digital light processing bioprinting of hydrogel-based microfluidic chips. (24th November 2021) - Bhusal, Anant; Dogan, Elvan; Nguyen, Hai-Anh; Labutina, Olga; Nieto, Daniel; Khademhosseini, Ali; Miri, Amir K
Abstract: Recent advancements in digital-light-processing (DLP)-based bioprinting and hydrogel engineering have enabled novel developments in organs-on-chips. In this work, we designed and developed a multi-material, DLP-based bioprinter for rapid, one-step prototyping of hydrogel-based microfluidic chips. A composite hydrogel bioink based on poly-ethylene-glycol-diacrylate (PEGDA) and gelatin methacryloyl (GelMA) was optimized through varying the bioprinting parameters such as light exposure time, bioink composition, and layer thickness. We showed a wide range of mechanical properties of the microfluidic chips for various ratios of PEGDA:GelMA. Microfluidic features of hydrogel-based chips were then tested using dynamic flow experiments. Human-derived tumor cells were encapsulated in 3D bioprinted structures to demonstrate their bioactivity and cell-friendly environment. Cell seeding experiments then validated the efficacy of the selected bioinks for vascularized micro-tissues. Our biofabrication approach offers a useful tool for the rapid integration of micro-tissue models into organs-on-chips and high-throughput drug screening platforms.